2011
DOI: 10.1093/infdis/jir096
|View full text |Cite
|
Sign up to set email alerts
|

Global Eradication of Measles: An Epidemiologic and Economic Evaluation

Abstract: In conclusion, the study found that, compared to the baseline, reaching measles eradication by 2020 would be the most cost-effective measles mortality reduction scenario, both for the six countries and on a global basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 4 publications
0
71
2
4
Order By: Relevance
“…5,12,18 In this study, we found that from 2011-2015 a unit change of doses of measles vaccines administered into the population reduced the risk of measles by 30%. A yearly analysis however indicated excess risk due to vaccine administration usually when only outbreak response were conducted in most part of the year as reflected in the increasing burden of the disease among vaccinated population in 2011, 2013 and 2014.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…5,12,18 In this study, we found that from 2011-2015 a unit change of doses of measles vaccines administered into the population reduced the risk of measles by 30%. A yearly analysis however indicated excess risk due to vaccine administration usually when only outbreak response were conducted in most part of the year as reflected in the increasing burden of the disease among vaccinated population in 2011, 2013 and 2014.…”
Section: Discussionmentioning
confidence: 58%
“…In recent times, similar factors have accounted for the occurrence of outbreaks in both developing and underdeveloped countries. 10,11,[16][17][18][19] Comparing the risk of measles among vaccinated population over time was limited by possible recall bias since vaccination status of cases was not evidenced by card and detailed history of vaccine handling. Therefore, the extent of variation of trends that could be attributed to vaccine failure may be deficient but possibly cannot be discounted considering the weak health system.…”
Section: Discussionmentioning
confidence: 99%
“…Students have measles more often that other groups, which proves the need of their vaccination as a matter of priority. [1,6,12,13] The objective of our research was the assessment of epidemiological situation on measles in one of regions of the Republic of Kazakhstan.…”
Section: Original Articlementioning
confidence: 99%
“…As coverage declines large-scale outbreaks are inevitable. Economic modeling has demonstrated that a coordinated campaign achieving global interruption of measles virus circulation by 2020 would result in a massive return on investment freeing up considerable finances currently required for treating hospitalized cases and responding to outbreaks [24]. However any decrease in the level of investment will rapidly result in a rebound of cases and deaths with a catastrophic loss of recent gains [11].…”
Section: The Duty Of Care and Rule To Rescuementioning
confidence: 99%